Diarylethene Self‐Assembled Monolayers: Cocrystallization and Mixing‐Induced Cooperativity Highlighted by Scanning Tunneling Microscopy at the Liquid/Solid Interface. Issue 32 (26th June 2015) - Frath, Denis; Sakano, Takeshi; Imaizumi, Yohei; Yokoyama, Soichi; Hirose, Takashi; Matsuda, Kenji
Abstract Stimulus control over 2D multicomponent molecular ordering on surfaces is a key technique for realizing advanced materials with stimuli‐responsive surface properties. The formation of 2D molecular ordering along with photoisomerization was monitored by scanning tunneling microscopy at the octanoic acid/highly oriented pyrolytic graphite interface for a synthesized amide‐containing diarylethene, which underwent photoisomerization between the open‐ and closed‐ring isomers and also a side‐reaction to give the annulated isomer. The nucleation (Kn) and elongation (Ke) equilibrium constants were determined by analysis of the concentration dependence of the surface coverage by using a cooperative model at the liquid/solid interface. It was found that the annulated isomer has a very large equilibrium constant, which explains the predominantly observed ordering of the annulated isomer. It was also found that the presence of the closed‐ring isomer induces cooperativity into the formation of molecular ordering composed of the open‐ring isomer. A quantitative analysis of the formation of ordering by using the cooperative model has provided a new view of the formation of 2D multicomponent molecular ordering.